Zero-rating and vertical content foreclosure - Thomas D. Jeitschko; Soo Jin Kim; Aleksandr Yankelevich (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
We study zero-rating, a practice whereby an Internet service provider (ISP) that limits retail data consumption exempts certain content from that limit. This practice is particularly controversial when an ISP zero-rates its own vertically integrated content, because the data limit and ensuing overage charges impose an additional cost on rival content. We find that zero-rating and vertical integration are complementary in improving social welfare, though potentially at the expense of lower profit to an unaffiliated content provider. Moreover, allowing content providers to pay for zero-rating via a sponsored data plan raises welfare by inducing the ISP to zero-rate more content.
Keywords: D43; L11; L42; 330; Data Caps; Sponsored Data; Two-Sided Market; Vertical Content Foreclosure; Zero-Rating